Investment Attractiveness of the Hotel, Restaurant and Tourism Business in Ukraine: Financial Indicators of Internal Threats - Лариса Докієнко; Віктор Тринчук (Ресторанний і готельний консалтинг: Інновації, 2022)
Topicality. In the current realities of Covid-19 pandemic and martial law in Ukraine, every enterprise must focus on the processes transformation of provision and development, which allow to quickly respond to their activity, challenges and modifications in order to be attractive for investment.